2009
DOI: 10.1063/1.3240198
|View full text |Cite
|
Sign up to set email alerts
|

Gauge origin independent calculations of nuclear magnetic shieldings in relativistic four-component theory

Abstract: The use of perturbation-dependent London atomic orbitals, also called gauge including atomic orbitals, has proven efficient for calculations of NMR shielding constants and other magnetic properties in the nonrelativistic framework. In this paper, the theory of London atomic orbitals for NMR shieldings is extended to the four-component relativistic framework and our implementation is described. The relevance of London atomic orbitals in four-component calculations as well as computational aspects are illustrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 109 publications
0
70
0
Order By: Relevance
“…͑27͒ with Eq. ͑28͒ shows that the combination of GIAO and MB brings in no complications, contrary to the statement made by Ilias et al 59 Instead, the GIAO-LRT is still very demanding on the RKB basis sets ͑vide post͒ and is thus not recommended for practical applications.…”
Section: ͑28͒mentioning
confidence: 86%
See 1 more Smart Citation
“…͑27͒ with Eq. ͑28͒ shows that the combination of GIAO and MB brings in no complications, contrary to the statement made by Ilias et al 59 Instead, the GIAO-LRT is still very demanding on the RKB basis sets ͑vide post͒ and is thus not recommended for practical applications.…”
Section: ͑28͒mentioning
confidence: 86%
“…It will be shown that the calculated NMS tensors are not only independent of the choice of gauge origin but also converge rapidly to the basis set limit. Note in passing that Quiney et al [13][14][15] and Ilias et al 59 also adopted the GIAO method in their uncoupled-DHF or CP-DHF but they did not take the MB into account.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Iliaš et al stated that the CGO should be placed at atom I in the H NMR calculation for a HI molecule [3]. According to their interpretation [3] and that of Malkina et al [29], the shielding of the hydrogen nucleus is caused by the electronic cloud of iodine only. That is, when the gaugeorigin dependence from the neighboring atoms is negligible, the CGO should be placed at the resonant atom position.…”
Section: Hydridesmentioning
confidence: 99%
“…On the other hand, the DKH2-BP method provides the gauge-origin invariant NMR values and the DKH-BP values agree well with the 4c reference values. Clearly, the CGO should be placed at the X position, as stated by both Iliaš et al [3] and Malkina et al [29]. In addition, unlike the I NMR calculations for HI, the gauge-origin dependence of the H NMR values is eliminated by the DKH2-CGO-WTBS method.…”
Section: Hydridesmentioning
confidence: 99%
See 1 more Smart Citation